News in Brief - Marchese Morales, Adolfo (2013)
This section contains a small compilation of news and events that took place in Peru and that are interesting from a chemistry perspective. Of 2013 we have highlighted the Minamata Convention on Mercury, the ANR prize to Nadia Gamboa, Chemistry lecturer at PUCP, the SUNAT’s new decree to control chemical supplies and the production status of the Chemical Industry, among others.